82 Bariatric surgery reverses ventricular repolarisation heterogeneity – mechanistic insights into fat-related arrhythmic risk. (6th June 2022) - Patel, Kiran; Bajaj, Nikesh; Statton, Ben; Herath, Nihara; Li, Xinyang; Davidson, Ross; Savvidou, Stelutsa; Coghlin, Joseph; Stoks, Job; Purkayastha, Sanjay; Cousins, Jonathan; Ware, James; et al.
Abstract : Background: Obesity confers higher risks of atrial arrhythmias and sudden cardiac death. Despite this, the proarrhythmic substrate in obesity and its reversibility with weight loss has not been studied in-depth. To address this, the proarrhythmic substrate in obese patients, and its reversibility with bariatric surgery, was characterised using electrocardiographic imaging (ECGi). Methods: ECGi was performed in 16 obese patients pre-bariatric surgery (PreSurg; mean age 43+12 years, 13 female) and 16 age- and sex-matched non-obese (lean) individuals (42+11 years). 12/16 obese patients also underwent ECGi after surgery (PostSurg). Over 2000 atrial and ventricular epicardial electrograms were computed using high density body surface mapping (256-lead ECG) and heart-torso geometries from cardiac magnetic resonance imaging, by solving the inverse problem of electrocardiography. Local atrial and ventricular epicardial activation times (AT) were calculated as the steepest downslope of their respective activation complexes, and local ventricular repolarisation times (RT) as the steepest upslope of the T-wave. Atrial activation gradients (ATG) and ventricular repolarisation gradients (RTG) were calculated as the maximum difference within 10 mm radius divided by the corresponding distance. Results: BMI was greater in PreSurg vs lean (46.7+5.5 vs 22.8+2.6kg/m2, p<0.0001) and decreased with surgery (PostOb 36.8+6.5kg/m2, p<0.0001). Epicardial adipose tissue (EAT) was greater in PreSurg vs lean (83+56 vs 28+13 ml, p<0.0001) and decreased post-surgery (PostSurg 69+45 ml, p=0.0010). Total atrial AT was prolonged in PreSurg vs lean (62+15 vs 46+12 ms, p=0.0028), which persisted post-surgery (PostSurg 67+15 ms, p=0.86). Atrial ATG were also greater in PreSurg vs lean (26+11 vs 14+8 ms, p=0.0007) and did not change with weight loss (PostSurg 25+12, p=0.44). Ventricular RTG were greater in PreSurg vs lean (26+11 vs 15+7 ms/mm, p=0.0024) and decreased with weight loss (PostSurg 19+8, p=0.0009), and were similar between PostSurg and lean (p=0.20). EAT correlated with atrial ATG (r=0.36, p=0.044) and ventricular RTG (r=0.54, p=0.0014). Ventricular AT was similar between lean (31+6 ms), PreSurg (34+5 ms) and PostSurg (35+9 ms); all p>0.05. Conclusion: Bariatric surgery in obese patients reduces ventricular repolarisation heterogeneity that may be partly explained by regression of epicardial fat. Atrial activation remains prolonged in obesity post-bariatric surgery. These results provide mechanistic insights into obesity-related arrhythmic risks and its reversibility with bariatric surgery. Conflict of Interest: Nil